Flexible sensor concept and an integrated collision sensing for efficient human-robot collaboration using 3D local global sensors - Rashid, Aquib; Alnaser, Ibrahim; Bdiwi, Mohamad; Ihlenfeldt, Steffen (Frontiers in Robotics and AI, 2023)
Human robot collaboration with traditional industrial robots is a cardinal step towards agile manufacturing and re-manufacturing processes. These processes require constant human presence, which results in lower operational efficiency based on current safety standards. The workspace of the human is fixed with clear task division with the industrial robot. The work proposes a novel local and global sensing framework, which discusses a flexible sensor concept comprising of a single 2D or 3D LiDAR, while formulating occlusion due to robot body. Moreover, this work extends the previous local global sensing methodology to incorporate local 3D sensor on the robot body. One of the main aims is to have minimum scalable sensor concept and adjust according to the process requirements. The local 3D camera faces towards the robot shadow area, which ensures minimum occlusion in the robot workspace. An efficient and generic method is proposed, to estimate the intrusion distance and reaction time parameters for the sensing system. The proposed methodologies are implemented with heavy-duty industrial robot along with 8-channel LiDAR and 3D camera. The resulting system enables high robot velocities while providing flexibility and safety with heavy-duty industrial robots.